A double ouroboros-shaped noncovalent molecular dimer. Issue 17 (19th April 2023) - Kedia, Moon; Soumya, K. R.; Phukon, Upasana; Mishra, Isha; Borkar, Reema L.; Vengadeshwaran, Palanichamy; Bhol, Mamina; Sathiyendiran, Malaichamy
Abstract : A double ouroboros-shaped molecular dimer stabilized via complementary intermolecular contacts was crystallized from a tripodal molecule having the ability to adopt conformation similar to molecular tweezers at one end and a lone unit at the other. Abstract : A double ouroboros-shaped molecular dimer was crystallized from a tripodal molecule having the ability to adopt conformation similar to molecular tweezers at one end and a lone unit at the other. Two complementary tripodal molecules self-organize into a dimer like two serpents biting each other's tails in a circular fashion.